The Relationship between Motivation and Competence on the Performance of State Senior High School Teachers in the Salibabu Islands, Talaud Islands Regency - Deasy Virginia Katiandagho; Mozes M. Wullur; Mario Tulenan Parinsi (International Journal of Information Technology and Education, 2026)
This study aims to determine whether there is a relationship between motivation and competence on the performance of public high school teachers in the Salibabu Islands, Talaud Islands Regency. This study used a correlational study with a population of 76 ASN teachers from three schools. A total of 30 teachers were used as a trial, and a sample of 46 teachers was taken. Three research instruments were used: motivation, competence, and teacher performance in the form of a questionnaire. The results of the study are as follows. First, this study found a relationship between motivation (X1) and teacher performance (Y) in public high schools in the Salibabu Islands, Talaud Islands Regency, where Y ̂ = 67.41 + 0.41X and a hypothesis value of 15.54 > 4.06. Second, in line with these findings, it was also found that there is a relationship between competence (X2) and teacher performance (Y) in public high schools in the Salibabu Islands, Talaud Islands Regency, where Y ̂ = 71.13 + 0.35X and a hypothesis value of 6.08 > 4.06. Third, this study also found a simultaneous relationship between motivation (X1) and competence (X2) with teacher performance (Y) at public high schools in the Salibabu Islands, Talaud Islands Regency, where Y = 61.2 + 0.37X_1 + 0.10X_2, and the hypothesis value is 7.87 > 3.21.